El‐bâkillanî’ye atıfları çerçevesinde el‐gazzâlî’nin fıkıh usûlünde muhakkikliği - (:unkn) unknown (My University, 2012)
el‐Gazzâlî’nin Fıkıh usûlü ilminde tahkik ehlinden olup olmadığını tespit edebilmekiçinöncekiulemayaaitgörüşlerinasıldeğerlendirdiğini,kendisin‐ denyaklaşıkbirasırönceyaşamışel‐Bâkıllânî’yeyaptığıatıflarçerçevesinde elealdık.Makaleninbaşındaherikimüellifin,Fıkıhusûlüsahasındakikonum‐ larınıortayakoyanbilgilereyerverdik.Dahasonrael‐Bâkıllânî’ningörüşleri‐ nin el‐Gazzâlî’ye nasıl intikal ettiğine temas ettik. Nihayet el‐Gazzâlî’nin el‐ Bâkıllânî’ye yaptığı atıfları, “el‐Bâkıllânî’nin görüşüne katıldığı, ondan farklı düşündüğüvetemelyaklaşımdaaynıolmaklabirliktebazıteferruattaondan ayrıldığıhususlar”şeklindeüçayrıbaşlıkaltındadeğerlendirdik.

We have examined whether or not al‐Ghazzâlî was a man of investigation tahqiq according to methodology of Islamic Jurisprudence and how he evaluated the former scholars’ views based on his references to al‐Bâqillânî, a scholar who lived about a century before him. At the beginning of our article, we have presented information about these two scholars’ positions within methodology of Islamic Jurisprudence. Then, we have dealt with how al‐ Bâqillânî’s views were transmitted to al‐Ghazzâlî. Finally, we have evaluated al‐Ghazzâlî’s references to al‐Bâqillânî under three separate sub‐sections as “al‐Bâqillânî’s views agreed by al‐Ghazzâlî, his views disagreed by al‐Ghazzâlî, and his views that are fundamentally agreed by al‐Ghazzâlî but have some dif‐ ferences in details.”
al‐Ghazzâlî as an investigator of usûl al‐fiqh in the light of his attributions to al‐Bâqillânî
Keywords: Din Bilimi